2014
DOI: 10.1186/1471-2164-15-113
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variations of the extensively amplified Y-linked genes, HSFY and ZNF280BY, in cattle and their association with male reproductive traits in Holstein bulls

Abstract: BackgroundRecent transcriptomic analysis of the bovine Y chromosome revealed at least six multi-copy protein coding gene families, including TSPY, HSFY and ZNF280BY, on the male-specific region (MSY). Previous studies indicated that the copy number variations (CNVs) of the human and bovine TSPY were associated with male fertility in men and cattle. However, the relationship between CNVs of the bovine Y-linked HSFY and ZNF280BY gene families and bull fertility has not been investigated.ResultsWe investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 42 publications
2
65
1
Order By: Relevance
“…Consistently, PLA2G2D was found to be located in CNVR 22, whose number of repeats can significantly reduce the mRNA levels of PLA2G2D and correspondingly cause growth retardation in Chinese cattle21. Yue et al 4142. studied Holstein bulls and found that the PRAMEY copy number is negatively correlated with scrotal circumference, relative scrotal circumference, percentage of normal sperm, and nonreturn rate, and the CNVs of both HSFY and ZNF280BY are negatively correlated with testis size and positively correlated with sire conception rate.…”
Section: Discussionmentioning
confidence: 90%
“…Consistently, PLA2G2D was found to be located in CNVR 22, whose number of repeats can significantly reduce the mRNA levels of PLA2G2D and correspondingly cause growth retardation in Chinese cattle21. Yue et al 4142. studied Holstein bulls and found that the PRAMEY copy number is negatively correlated with scrotal circumference, relative scrotal circumference, percentage of normal sperm, and nonreturn rate, and the CNVs of both HSFY and ZNF280BY are negatively correlated with testis size and positively correlated with sire conception rate.…”
Section: Discussionmentioning
confidence: 90%
“…Some of these genes are crucial for fertility: these include AZF1 (azoospermia factor 1), BPY2 (basic protein on the Y chromosome), DAZ1 (deleted in azoospermia), TSPY (testis specific protein), UTY (ubiquitously transcribed TPR gene on the Y chromosome), SRY (sex-determining region); Y chromosome also contains so-called male-specific regions associated with increased risk of cardiovascular disease or testis and prostate cancer [46][47][48]. Most of data associated with animals male reproductive traits came from studies on mouse, less from studies on rat or cattle [49][50][51]. Also in animals, some of Y-chromosomal genes are needed for proliferation of spermatogonial stem cell and normal sperm morphology [49], some of them could be functional in rat and non-functional in mouse [50] or are highly conserved in some mammalian species [52].…”
Section: Discussionmentioning
confidence: 99%
“…Cattle also have a documented expansion of HSFY (Hamilton et al 2011; Yue et al 2014), also with no apparent corresponding HSFX expansion on the X chromosome. This opened the possibility that the amplification predated the bovine/suid divergence, and was then maintained in each lineage.…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian HSFY seems present in low but variable copy number across many species, with between two and eight copies in cats (Pearks Wilkerson et al 2008; Murphy et al 2006), at least one retroposed active copy in mice (Kinoshita et al 2006) and the two active copies in humans (Tessari et al 2004) plus several pseudogene copies, one of which is found on chromosome 22. In cattle, the gene family has amplified to at least 70 copies (Hamilton et al 2011; Yue et al 2014). Recent work suggests that the amplification in cattle occurred after their divergence with sheep, and so is likely an independent amplification to that in pigs (Chang et al 2013).…”
Section: Introductionmentioning
confidence: 99%